Pengaruh Minat Siswa Kelas X terhadap Pembelajaran Renang di SMAN 2 Purwakarta - Diki Herwanto; Abduloh Abduloh; Rolly Afrinaldi (Peneliti.net, 2021)
This study aims to reveal data information about the effect of interest in class X students on learning to swim at SMAN 2 Purwakarta. This study uses a quantitative approach because the data in this study are centered on numbers and data management uses descriptive statistical analysis to arrive at the conclusions of the research results. The results showed that the interest of class X students of SMAN 2 Purwakarta in learning swimming was measured by a questionnaire totaling 26 items and the respondents who were examined were 100 students of class X MIPA